中国汽车工业的产业结构及其调整战略 = The industrial structure of China's automobile industry and its reform - 王舜 Wang, Shun (2010)
这项研究旨在找出它的发展之前和之后的市场化改革，对中国汽车产业的工业结构的特点。本研究的重点是与中国汽车业与世界汽车行业的生产集中和营销策略上的比较。这一发现是， 中国汽车行业的特点是，因为太多的企业，过于分散地域，太行之间的生产企业分离。这些功能极大地限制从与世界市场的国际汽车跨国公司竞争的中国汽车产业。为改善中国汽车产业的工业结构的几点政策建议提出的结论。 This study aims at identify the features of industrial structure of the Chinese automobile industry from its development before and after the market-oriented reforms. The focus of this study is the comparison between the Chinese automobile industry and the world automobile industry in terms of production concentration and marketing strategies. The finding is that the Chinese automobile industry is featured as too many firms, too fragmented geographically, too isolated between firms in production corporation. These features dramatically constrained the Chinese automobile industry from competing with the international automobile MNCs in the world market. Some policy suggestions for improving the industrial structure of the Chinese automobile industry are presented in the conclusion.